Perovskites : structure-property relationships - Tilley, R. J. D. (Chichester, West Sussex, United Kingdom : Wiley, 2016)
Uniquely describes both the crystallography and properties of perovskite related materials. -Practical applications in solar cells, micrulectronics and telecommunications -Interdisciplinary topic drawing on materials science, chemistry, physics, and geology -Contains problems and answers to enhance knowledge retention.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Perovskite; Perovskite; NATURE / Rocks & Minerals; SCIENCE / Earth Sciences / Mineralogy; Electronic books; Electronic books